Variation and Molecular Basis for Enhancement of Receptor Binding of H9N2 Avian Influenza Viruses in China Isolates - Liu, Yang; Li, Shuo; Sun, Huapeng; Pan, Liangqi; Cui, Xinxin; Zhu, Xuhui; Feng, Yaling; Li, Mingliang; Yu, Yanan; Wu, Meihua; Lin, Jiate; Xu, Fengxiang; et al. (Frontiers in Microbiology, 2020)
Currently, H9N2 avian influenza viruses (H9N2 AIVs) globally circulate in poultry and have acquired some adaptation to mammals. However, it is not clear what the molecular basis is for the variation of receptor binding features of the H9N2 AIVs. The receptor binding features of 92 H9N2 AIVs prevalent in China during 1994-2017 were characterized through solid-phase ELISA assay and reverse genetics. H9N2 AIVs that circulated in this period mostly belonged to Clade h9.4.2. Two increasing incidents occurred in the ability of H9N2 AIVs to bind to avian-like receptors in 2002-2005 and 2011-2014. Two increasing incidents occurred in the strength of H9N2 AIVs to bind to human-like receptors in 2002-2005 and 2011-2017. We found Q227M, D145G/N, S119R, and R246K mutations can significantly increase H9N2 AIVs to bind to both avian-like and human-like receptors. A160D/N, Q156R, T205A, Q226L, V245I, V216L, D208E, T212I, R172Q, and S175N mutations can significantly enhance the strength of H9N2 AIVs to bind to human-like receptors. Our study also identified mutations T205A, D208E, V216L, Q226L, and V245I as the key sites leading to enhanced receptor binding of H9N2 AIVs during 2002-2005, and mutations S119R, D145G, Q156R, A160D, T212I, Q227M, and R246K as the key sites leading to enhanced receptor binding of H9N2 AIVs during 2011-2017. These findings further illustrate the receptor binding characteristics of avian influenza viruses, which can be a potential threat to public health.